2020
DOI: 10.3390/fluids5040177
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cross Level Air Interaction within Multilevel Underground Carparks on Indoor Air Quality

Abstract: Ventilation for underground carparks is critical to indoor air quality (IAQ) due to carbon monoxide (CO) emissions from cars. The IAQ within a multi-level underground carpark of a shopping mall has been investigated using computational fluid dynamics (CFD) model based on ANSYS-FLUENT (18.1) software. The effects of car engines types, porosity of supply and exhaust air louvers and ventilation flow rates on IAQ were examined. A mesh sensitivity study was conducted and the CFD model was validated against the full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…The choice of ANSYS-Fluent to provide this study was driven by its extensive usage and established reputation, as demonstrated by its consistent application in earlier research conducted by several researchers in the field of ventilation [12][13][14][22][23][24][25][26][27][28].…”
Section: Model Descriptionmentioning
confidence: 99%
“…The choice of ANSYS-Fluent to provide this study was driven by its extensive usage and established reputation, as demonstrated by its consistent application in earlier research conducted by several researchers in the field of ventilation [12][13][14][22][23][24][25][26][27][28].…”
Section: Model Descriptionmentioning
confidence: 99%